Balancing Content & Language in the English Language Development Classroom - Reynolds-Young, Danielle; Hood, Sally (The ORTESOL journal, 2014)
As an instructor of courses in a university English as a Second Language (ESL) endorsement program (an 18-credit hour program that "adds" an endorsement to an initial teaching license, grades K-12), I find that ESL teacher candidates often ask how to develop curricula for an English Language Development (ELD) class. Questions arise as we critique former and current practices that lean toward teaching English grammar out of context (Ciechanowski, 2013; Mize & Dantas -Whitney, 2007). I design the ESL endorsement program courses so they are aligned with the NCA TE/TESOL ESL K-12 Teacher Education Program Standards (Teachers of English to Speakers of Other Languages, 2010). The authors of the standards endorse, with the support of numerous leaders in the ESL field, an ESL curriculum that is designed to teach language within the context of academic content (2010). Although course assignments require ESL teacher candidates to design activities, performance assessments, and lessons that balance the teaching of the English language and academic content, the ESL teacher candidates remain perplexed as to how to teach without a prescribed curriculum.